Building an institutional framework for monetary stability: the case of Italy (1979-1994) - PASSACANTANDO, F. (PSL Quarterly Review, 2013)
Italy's monetary regime has experienced significant developments from 1979 to 1994. The independence of the central bank from the government was strengthened by several reforms. The period under review is characterised by monetary policy consistent with the Italian government's inflation targets following the abandonment of the European Exchange Rate Mechanism in Sep. 1992. Factors leading to the replacement of one type of institutional arrangement by another and the effects on monetary policy performance are examined. The steps followed and the problems encountered in implementing a system which would ensure monetary stability are also presented. JEL Codes: E52, E58